PEMBUATAN MESINPOLES UNTUK PENGRAJIN PERAK DI KOTA GEDE, YOGYAKARTA GUNA MENINGKATKAN KAPASITAS EKSPORT - Widarto, Widarto (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2003)
The general   purpose of this program is to produce Polishing Machines for silver  planning  and  refining  work  as  art  craftsmanship  commodities.  The  special purpose  of  the  program  are  (I)    to  increase the   producing  capacity  of  silver craftsmanship  workers'   group;  and  (2)   to  improve  the  quality  and  quantity  of production to meet exporters' demand and requirements.Methods constructed  to  accomplish  the  mentioned  above  purpose  are  (I) to  planPolishing  Machines  model,  (2)   to  design  working  drawing,  (3)   to  make working schedule, (4) to plan cost, (5) to implement modeling, (6) to test and verify the machines,  (7)  correcting  insufficiencies,  (8)  to conduct    training  for  industrial operators, (9) to prepare final report.The  output  of    Vucer    Program  is  a  Polishing  Machines  with  followingtechnical specifications: (1)  Machine dimension = L x W x H : 2200  x 800  x  1000!TIm; (2)  Chassis = Profile iron L 32  mrn; (3)  Generating power = Electric motor  1 phase, nov,  Y2   HP,  1400  rpm;  (4)  Transmission  system = Using  pulley  without'coupling; (5)  Polishing disk  revolution =800  rpm; (6)  Working  hour  per day = 6 hours; (7)  Production capacity per day = 88 pieces; and (8)  Empirical age prediction of  machine  :=    ± 8  years.  The  comparison  before  and  after  using  the  Polishing Machine: (1) Production capacity per day, post-vucer 50 pieces, post-vucer 88 pieces; (2) Grossprofit  per day, pre-vucer Rp 50,000,  Rp 88,000;  (3) Operating cost perday, pre-vucer  Rp  15,000,  post-vucer. Rp 21,000;   (4)  Net profit   per day,  pre-vucer  Rp35,000,  post-vucer Rp 67,000;  (5) Net profit per month, pre-vucer Rp 875,000,   postvucer Rp r ,675,000;   (6) Profit difference per month = Rp 800,000;  (7) Machine price= Rp. 5,000,000;   and (8) BEP = 6,25 month. The conclusion of  Vucer Program is that: (1) The silver polishing machine is able to improve quality and quantity of product, (2) All machine components function as planned, and even allow for further development,  (3)  Machine. operation  is simple,  (4)  the  performance  is good  from technical point of view, (5)  from economic point of view, it is very feasible for the silver craftsmanship  workers. The vacuum cleaner  installation  is recommended  for optimal  use  of  this  machine.  It can  be  installed  by the  partner.  Furthermore,  the machine technology can be distributed to similar industries.Key words:   polishing machine, for silver,